Skin Cancer in Varanasi - Tripathi, F. M.; Khanna, S.; Khanna, N. N.; Sinha, J. K. (Indian Journal of Plastic Surgery, 1977)
In present study 100 cases of skin cancer over a period of three years have been studied. Diagnosis of each lesion is comfirmed by histology. Incidence of epithelioma of skin is much more as compared with basal cell carcinoma and melanoma. Various sites of these tumours are also noted. Lymph node metastasis is quite early in cases of melanoma.